Structural and Optical Properties of Pure and Mn2+ Doped CdS Nanocrystalline Thin Films Prepared by Chemical Bath Deposition - Abhilash1, K.P.; Kalaivani1, S.; Christopher Selvin1, P.; Nalini2, B.; K, K.; Somasundaram1, K. (Asian Journal of Chemistry, 2013)
The pure and Mn2+ doped CdS thin films were prepared by chemical bath deposition method. The effects of Mn2+ doping on CdS matrix have been investigated by studying the changes in the structural, morphological and optical properties of the sample. The X-ray diffraction results show that the CdS:Mn nanocrystalline thin films have a-CdS hexagonal phase with a strong orientation along the (0 0 2) direction. The incorporation of Mn2+ did not cause any change in the texture but reduces the intensity of the peak and it leads to a smaller crystalline size. The surface morphology and stoichiometry of the prepared samples were investigated using the SEM and EDX analysis. The absorption wavelength, band gap energies of the sample from the UV-Vis spectra were analyzed and reported. The photoluminescence characterization of the sample shows three emission peaks at 544, 620 and 670 nm due to the band edge related surface defect states, Mn2+ impurities and sulphur vacancies respectively. The films show enhanced emission intensity with increase in Mn2+ concentration.